Sarcopenia and risk of nonalcoholic fatty liver disease: A meta-analysis - Karn Wijarnpreecha (2018)
© 2018 Saudi Journal of Gastroenterology Published by Wolters Kluwer-Medknow. Background/Aim: The association between sarcopenia and nonalcoholic fatty liver disease (NAFLD) has been suggested by recent epidemiological studies, although the results have been inconsistent. This meta-analysis was conducted to summarize all available data and estimate the risk of NAFLD among patients with sarcopenia. Materials and Methods: A comprehensive literature review was conducted using MEDLINE and EMBASE databases through November 2016 to identify all studies that compared the risk of NAFLD among patients with sarcopenia versus those without sarcopenia. Effect estimates from each study were extracted and combined using the random-effect, generic inverse variance method of DerSimonian and Laird. Results: Five cross-sectional studies with 27,804 participants met the eligibility criteria and were included in the meta-analysis. The risk of NAFLD in patients with sarcopenia was significantly higher than those without sarcopenia with the pooled odds ratio of 1.54 (95% confidence interval, 1.05-2.26). The statistical heterogeneity was high with an I2of 83%. Conclusions: A significantly increased risk of NAFLD among patients with sarcopenia was observed in this study.